(untitled) (Jurnal Agroekoteknologi dan Agribisnis, 2022)
Shallot peeling in small scale industries are usually done manually. This process requires a lot of time and effort. In order to obtain time efficiency, the dehulling machine with low electric power and easy to use is needed. This study aimed to produce a shallot dehulling machine at PT Bahagia Jaya Sejahtera using the concept of machine design and manufacture. The tools used were workshop tools and the materials were stainless plats and angle iron. The production process started after the design is finished and approved. This process included the making of dehulling chamber, inlet, outlet, and machine frame. Then, those parts were assembled and properly furnished. The product then was tested its functional design to observe its working ability. Functional tests were conducted without and with shallots. The test without shallots showed that each component worked well. The test with shallots showed that the modification was needed for some parts to improve its functions.